The lives of a Filipino/a high school student anthology of personal essays on high school in the Philippines - Tolentino, Roland B.; Delos Reyes, Joselito D.; Jarin, Ferdinand Pisigan (Manila, Philippines University of Santo Tomas Publishing House, 2022)
"The essays are touching tributes to the multitudes coming into being as high school students, and to the lives prior to the addition of two years of schooling as mandated for global competitiveness. Ours was a simpler time when the public schools excelled, private education was more liberal; and when despite restrictions, young individuals were able to negotiate their tribulations, make do with what is available, and set forth their dreams that forever marked and guided us in our adult life."--Back cover.

"These are elegies to an era worth remembering, writing, and memorializing. Even as the older styled high school is gone, this anthology of personal essays brings this momentous event to life and literature. We do remember, we will not forget" --Back cover.
Introduction -- The Lives of a Filipino/a High School Student: Anthology of Personal Essays on High School in the Philippines / by Rolando B. Tolentino -- High School Life / Ricky Baizas -- The Queen's Speech / Ronald Baytan -- Board Work / Augusto Antonio A. Aguila -- War and Peace / Gabriela Lee -- Katey-Oh / Shane Carreon -- PPHS Class '57 Tales and Trivia / Fina Canave, Ricardo D. Ferrer, Jaime Tanigue, Ruperto E. Palisoc -- School Days / Luis V. Teodoro -- Choose Something like a Star / Gemino H. Abad -- Boys vs. Girls / Butch Dalisay -- Little Seeds of Rebellion / Marra PL. Lanot -- Diary and Scrapbook of a High School Freshman / Cristina Pantoja Hidalgo -- Going Feral / Mayette Q. Tabada -- How to Spot a Theresian in the Wild, Specifically the Breed Released in 1999 / Dawn Laurente Marfil -- Whare I Lived / Jose Wendell P. Capili -- A Piece of Who I Am / Anna Cris L. Langaoan -- The White Blouse / Jeena Rani Marquez -- Bless This Food / Jenny Ortuoste -- The Magical Mysteries of Tight-Fitting Jeans / Sarah F. Lumba -- Fatigues / Jose Victor Z. Torres -- The Fast Lane / Patricia C. Verzo -- Jhoanna's Johari Window / Jhoanna Lynn B. Cruz -- That's What Friends Are For / Arnie Q. Mejia -- Black Belt / Denver Ejem Torres -- Remembering Negros Occidental High School: Far Above Where Kanlaon Sits / Judy M. Taguiwalo -- Not a High School Horror Story / Joi Barrios -- Teenage Stress, Pre-EDSA Woes, and High School / Geraldine Kay P. Rodriguez -- Of Raging Hormones and National Liberation Struggles / Sarah Raymundo -- Wika / Adjani Guerrero Arumpac -- Fire Deferred / Januar Yap -- Quitters / John Bengan -- Final Friends / Anna Felicia C. Sanchez -- Best Friend / Louise Jashil R. Sonido -- Verbum Sat Sapienti / Frank Cimatu.
Keywords: High school students -- Philippines; Philippine essays (English)